BIBLIOMETRIC ANALYSIS OF SCIENTIFIC RESEARCH ON ENVIRONMENTAL AUDIT - Samusevych, Y.V.; Tenytska, I.A.; Vostrykov, P.M. (Socio-economic relations in the digital society, 2022)
Excessive use of the environment has raised concerns about its protection. Over time, and especially in recent years, the topic of environmental audit has become more important, being a topic of interest to companies, governments and the public. This was due to disproportionate growth in production, increasing the world economy. In this context, governments are committed to regulating the proper use and treatment of the environment. There is a special problem in this issue, contradictions between companies, governments, due to the assessment of damage and damage to the environment, analysis of the quantity and quality of preventive measures, and so on. Therefore, any activity of enterprises must be controlled, monitored, quantified, forecast and so on. An environmental audit is one of the mechanisms of such a comprehensive analysis. Based on this, we conducted a bibliometric analysis of the concept of "environmental audit" using SciVal tools from Elsevier. This allowed us to analyze the most relevant and cited works of scientists in the field of environmental audit. In addition, the areas of research that study environmental audit were identified, the main ones being: the field of ecology, energy and engineering. This state of affairs has confirmed the importance of environmental audits for conserving energy resources and finding the latest engineering solutions to reduce excessive production impact on the environment. The main subject areas of not only environmental audit but also environmental taxation and reporting were also studied, which allowed asserting the mutual influence of such concepts on the quality of environmental data. In general, we note that the results of the analysis confirm the relevance of the topic of environmental audit due to the dynamics of increasing the number of publications for the period from 2010 to 2021 compared to environmental taxation and reporting. In addition to Elsevier’s SciVal toolkit, tools such as Google trends were also used. The dynamics of Internet inquiries have confirmed the fact that their number is increasing due to global climate change or changes in legislation relating to environmental regulations and changes in tax rates. The presented verified data can be used in further studies to assess the impact of environmental audit on environmental quality.